Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Kemuhammadiyahan Melalui Model Pembelajaran Snowball Throwing Di Madarasah Aliyah Muhammadiyah 1 Medan - Dianto Dianto (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
The purpose of this study was to determine student learning outcomes using the Snowball Throwing method on the subject of the Muhammadiyah Academy in Madarasah Aliyah Muhammadiyah 1 Medan. This research is expected to be useful for teachers, schools and future researchers. For teachers, the results of this study are expected to be useful for teachers to improve teaching skills, especially in terms of innovative learning models. The methodology in this research is field research that is obtained through classroom action research (CAR) or called classroom action research. This research method uses two cycles. In the first cycle consists of the planning phase (planning), the stage of action / implementation (action), the stage of observation (observation), and the stage of reflection. Then in the second cycle carried out after learning in the first cycle was analyzed and reflected in order to correct the deficiencies that existed in cycle I. The results showed that the Class X learning outcomes using the Snowball Throwing model were higher than those who did not use them.